Immune-stimulatory effects of Fomes fomentarius extract in murine macrophages - Kim, Y.H.; Park, E.G.; Batsuren, D.; Ganbaatar, J.; Nho, C.W.; Pan, C.-H.; Lee, J.K. (Korean Society for Applied Biological Chemistry, 2014)
In this study, we demonstrated whether the extract of Fomes fomentarius (FFE; FF extract) could be used to stimulate macrophages (RAW 264.7 cells). All four doses of FFE (5, 10, 20, and 40 μg/mL) had no significant cytotoxicity during the entire experimental period. FFE potently increased the production of nitric oxide (NO). Consistent with these observations, inducible NO synthase levels were increased by FFE in a dose-dependent manner. Moreover, FFE increased the production of tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 in the same cells. These stimulating effects of FFE were found to be caused by the stimulation of phosphorylation of IκBα and MAP kinases (p38, ERK, and JNK). These results suggest that FFE may be used as new agents for wide application in the immune study of mushroom. ？ The Korean Society for Applied Biological Chemistry 2014.
Keywords: Fomes fomentarius; Murinae